National farm assurance scheme demonstrates welfare outcome improvements for sustainable intensification of dairy production. Issue 4 (4th July 2022) - Mullan, Siobhan; Wiltshire, Philippa; Cross, Kate; Main, David CJ; Still, Kate; Crawley, Madeleine; Dowsey, Andrew W.
ABSTRACT : Animal welfare is a key pillar of sustainability in livestock farming but can be challenging to deliver improvements when productivity is high. In October 2013, the Red Tractor UK national dairy assurance scheme introduced welfare outcome monitoring on its 11, 500 farms, covering 95% of UK milk produced. Here we show that 98 farm assurance assessors achieved high levels of agreement with a gold standard and report data they collected for three years from 248, 689 cows, typically 10 cows per farm, during 19, 899 audits. Between 2013 and 2014, and 2015 and 2016, the estimated national prevalence fell significantly for lameness (from 10.0% to 7.9%), dirtiness (from 12.4% to 9.2%), 'hairloss, lesions and swellings' (from 9.3% to 6.5%), and fat cows (from 2.4% to 1.9%). This occurred at a time when milk yield per cow increased. We have demonstrated an effective implementation strategy suitable for uptake internationally to align with societal sustainability goals. GRAPHICAL ABSTRACT: UF0001